Estudo de classificação e quantificação das lamas geradas no processo de beneficiamento de rochas ornamentais - Buzzi, Daniella Cardoso (2008)
In the city of Cachoeiro of Itapemirim, in the state of Espirito Santo, the processing sludge of ornamental stones (LBROs) produces a solid waste (RS) that impacts negatively on the environment because it is produced in large quantities and the state regulations regarding solid waste management arenot yet implemented in the law. Consequently, an inappropriate management of the LBROs occurs when most part of the rejected materials are put inside a tank open in the soil without any sort of protection, yielding soil and water reservoirs contamination. Facing this environmental impact, this research was conducted among a group of companies in the field of ornamental stone affiliated to AAMOL, located in the ciy of Cachoeiro Itapemirim, with the main purpose of classifying and quantifying the LBROs, according to NBR 10004/2004, 10005/2004 NBR, and NBR 10006/2004. To that end, it has a viable methodology for the RS management was developed. The methodology included the use of questionnaires and visits to AAMOL affiliated companies, quantification of blocks and polished plates and consumption of inputs in the process of unfolding. It also included the establishment of a sampling plan, according to the criteria established by the NBR 10007/2004, to collect samples of raw materials, inputs and LBROs. The classification of LBROs found that 77% of the samples were classified as Class IIA waste - Non-Inert waste and 23% as Class IIB - Inert, and the parameters Al, Ba, Cd, Pb, Cl-, Cr, phenol, Fe, F-, Hg, Ag, Na and SO4 2-, to measure the inert characteristic of the sample. There were also estimated , in this study, indicators of the amount of LBRO per unit deployed and polished plate in wetlands that are generated in the sludge, 95% and 99.7%, resulting in the ILD95% = 22.14 t / block, the ILP99,7% = 19,191 kg / plate, in addition to the indicators in the humidity of 30% maximum allowed for final disposal in landfills, resulting in the ILD30% = 14.76 t / block and ILP30% = 12,493 kg / plate, that have proven very to be effective in the dehydration process for the management of RS, since it allows better management and reduction in the cost of transportation and final disposal.